2015
DOI: 10.1016/j.aquaculture.2015.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing dietary levels of menhaden and soybean oils and soybean lecithin for pre-gonadal somatic growth in juveniles of the sea urchin Lytechinus variegatus

Abstract: Dietary lipids serve as important sources of energy and essential fatty acids for aquatic animals. Sources of animal and plant oils are increasingly limited as well as expensive, and dietary requirements associated with the inclusion of these oils must be carefully evaluated to facilitate sustainable and affordable formulations. In this study, we investigated quantities of menhaden oil (MO) with and without soybean lecithin or soybean oil (SO) to determine appropriate levels for optimal somatic growth for pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Consistently, Gibbs et al. (2015) found that WGR of juvenile Lytechinus variegatus fed SO was reduced compared to that fed FO, and further reduced with the increasing amount of SO. However, the present study showed no significance in the digestive capacity in response to different lipid sources.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Consistently, Gibbs et al. (2015) found that WGR of juvenile Lytechinus variegatus fed SO was reduced compared to that fed FO, and further reduced with the increasing amount of SO. However, the present study showed no significance in the digestive capacity in response to different lipid sources.…”
Section: Discussionmentioning
confidence: 59%
“…WGR of juvenile S. intermedius fed SO was lower than that fed LO and FO. Consistently,Gibbs et al (2015) found that WGR of F I G U R E 1 Transcription of fatty acid synthesis related genes in the intestine (a) and gonad (b) of juvenile sea urchin (Strongylocentrotus intermedius) in response to different lipid sources Transcription of major yolk protein (MYP) in the gonad and digestive tract of juvenile sea urchin (Strongylocentrotus intermedius) in response to different lipid sources Lytechinus variegatus fed SO was reduced compared to that fed FO, and further reduced with the increasing amount of SO.…”
mentioning
confidence: 58%
“…; Gibbs et al . ). In the current study, carbohydrate levels were adjusted by covarying the levels of acid‐washed diatomaceous earth.…”
Section: Discussionmentioning
confidence: 97%
“…The presence of biofilms 18 and in particular, specific metabolites released by bacteria and protozoans, are important settlement 19 cues for larvae of sponges 20 and an effect of chemical cues (e.g., humic acids, volatile infochemicals, ammonia and various ions, dissolved gases, organic compounds) on various invertebrate larvae 4,13,21 was demonstrated. A nearly universal mechanism of settlement induction by bacterial cues has been proposed, able to strongly influence such different taxa of invertebrates as cnidarians 17,22 , bryozoans 23 , molluscs 16 , annelids 24 , echinoderms 19,25 , crustaceans 26 and even ascidians 27 . A non-polar metabolite extracted from bacteria (Tetrabromopyrrole) 28 is also responsible for partial or complete metamorphosis in coral planulae, which demonstrated a highly specific response to single infochemicals 29 .…”
Section: Introductionmentioning
confidence: 99%